Distinct system-level computations underlie perceptual variation across the visual field - Shutian Xue; Antoine Barbot; Jared Abrams; Qingyuan Chen; Marisa Carrasco (Proceedings of the National Academy of Sciences, 2026)
Human visual perception for basic dimensions varies with eccentricity and polar angle, influencing daily activities such as reading, searching, and scene perception. We investigated whether and how system-level computations that transform visual input into perception underlie these heterogeneities. Using the equivalent noise method and perceptual template model, we estimated gain, internal noise, and nonlinearity for orientation discrimination across eccentricity (fovea, parafovea, and perifovea) and around polar angle. Participants discriminated the orientation of Gabors embedded in dynamic white noise and showed the expected variations across eccentricity and around polar angle. Importantly, visual performance declined with eccentricity due to decreased gain and nonlinearity and increased internal noise. Observers with stronger eccentricity effects showed greater gain decrease. Only gain varied with polar angle—higher along the horizontal than vertical meridian, and higher at the lower than the upper vertical meridian—paralleling performance asymmetries. This dissociation aligns with known variations in neuronal count and tuning. By revealing distinct system-level computations underlying the eccentricity effect and polar angle asymmetries, our findings link perceptual heterogeneity across the visual field and neural architecture and provide insights into how the human brain encodes information under neural constraints.